Avaliação andrológica comparativa entre varrões de alto mérito genético oriundos de linhagens puras e cruzadas - Poliana Campos Silva (2017)
Boars of different genotypes cannot be classified andrologically by the same system, since they have different growth rates and muscle tissue deposition. Thus, the use of a classification profile for each genotype makes the genetic selection process more efficient and adequate for each animal. This work was carried out with the purpose of comparing body and testicular development during the pre-pubertal phase, reproductive characteristics, such as precocity and libido, and seminal characteristics during puberty among two different strains. Two pure breeds used in the crossing of female lines (FL) and two lines of terminator cores (TL) were analyzed. Body weight and testicular measurements were taken in the first, third, and fifteenth weeks of life, reproductive characteristics were evaluated starting 21th week, and seminal parameters were collected weekly from the 24th until 30th week. Crossbred animals (TL) presented greater body weights and testicular measures (P < 0.01) compared to pure breed animals (FL). There was a trend (P = 0.07) for higher trainability of crossbred LT animals when compared to pure LM animals, as 97% of the LT males were trained, while 83% of the pure males LM were unable to mount the dummy. Genotype did not affect the seminal characteristics evaluated: volume, concentration, number of total spermatozoa, number of viable spermatozoa, motility and the percentage of normal spermatozoa in the morphological evaluation. LT crossbred males showed higher precocity and were approved in the seminal morphology evaluation at 26th week (185.5 days) compared to the pure LM that were approved latter than 29th week. Correlations were found between body weight in the first (r = 0.58, P < 0.001) and 15th (r = 0.39, P < 0.05) weeks and sperm concentration at the 28th week. Semen concentration at the 28th week was also correlated to the right testicle length (RTL) in the third week (r = 0.40, P < 0.05), right testicle width (RTW) at week 15 (r = 0.36, P < 0.05 ). There was a negative correlation between RTW at week 15 and age of approval (r = -0.32, P < 0.05) and a trend between body weight in the first week (r = - 0.28, P = 0.08) and body weight in the third week (r = - 0.28, P = 0.08) with age of approval. The results presented herein confirm the previous evidences of differences in growth development and sexual maturation between genotypes. Therefore, knowing the andrologic parameters of each genotype before and after puberty will help to establish specific high merit boars classification or declassification criteria, without the earlier and improper cull of good males